(untitled) (Agro Productividad, 2026)
Objective: To analyze the socioeconomic characteristics of the producers and the production system of the Apaxtleco chili in Apaxtla, Guerrero, Mexico. Design/Methodology/Approach: A structured questionnaire comprising both open- and closed-ended questions was administered, encompassing pre-production, production, post-harvest handling, and marketing components, in accordance with the methodology for evaluating agri-food chains to identify problems and propose projects. Additionally, the questionnaire assessed the social, economic, and productive attributes of the producers. For the evaluation of the production system, the Natural Resource Management Systems Evaluation Framework was applied. Results: The producers are predominantly older adults; 84% possess only basic education. They rely mainly on family labor, with 92% cultivating the Apaxtleco chili primarily for self-consumption, selling only the surplus, which results in minimal participation in the local market. The cultivated area ranges from 0.02 to 7.0 hectares. The production system remains traditional and is transmitted intergenerationally, forming part of the biocultural heritage of Apaxtla de Castrejón, Guerrero. Limitations of the Study/Implications: Due to regional insecurity, it was not feasible to interview all producers. Nonetheless, significant productive, social, and economic challenges among the surveyed producers were identified. Findings/Conclusions: The main constraints on the profitability of Apaxtleco chili cultivation in Apaxtla, Guerrero, include the advanced age and low educational attainment of producers, limited technology transfer, and insufficient government support. Furthermore, climatic challenges particularly droughts along with pest and disease control issues, the absence of a comprehensive technological package, marketing difficulties, and persistent insecurity and political instability in the region, collectively hinder development.